2002
DOI: 10.1016/s0022-2275(20)30470-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipopolysaccharide induces expression of ABCA1 but not ABCG1 via an LXR-independent pathway

Abstract: Two ATP-binding cassette transporter proteins, ABCA1 and ABCG1, may mediate an active efflux of cellular cholesterol and phospholipids. They are ubiquitously expressed and are subject to regulation by cholesterol loading or by treatment with agents that activate the nuclear hormone receptor LXR. Earlier studies in both primates and non-primates reported that treatment with endotoxin (bacterial lipopolysaccharide, LPS) reduces plasma levels of HDL cholesterol. To determine if such HDL reduction correlates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…We found that LPS increased mRNA levels of Abca1 ( Fig. 4A ), which was previously reported in the literature ( 50 ). We hypothesized that perhaps NRF2 activation could be connected to secretion of annexin A1 via ABCA1 induction.…”
Section: Resultssupporting
confidence: 90%
“…We found that LPS increased mRNA levels of Abca1 ( Fig. 4A ), which was previously reported in the literature ( 50 ). We hypothesized that perhaps NRF2 activation could be connected to secretion of annexin A1 via ABCA1 induction.…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, our result demonstrated that the expression of ABCG1 had no response to oridonin stimulation, which was not parallel with ABCA1. This phenomenon might be due to the underlying difference between ABCA1 and ABCG1, which was consistent with other groups' finding 31–33 . Thus, the beneficial effect of oridonin on lipid accumulation in macrophages might be contributed to the LXRα‐induced ABCA1 up‐regulation, but not ABCG1.…”
Section: Discussionsupporting
confidence: 90%
“…This phenomenon might be due to the underlying difference between ABCA1 and ABCG1, which was consistent with other groups' finding. 31 , 32 , 33 Thus, the beneficial effect of oridonin on lipid accumulation in macrophages might be contributed to the LXRα‐induced ABCA1 up‐regulation, but not ABCG1.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the transporter expression is probably carried out via the PPARa (peroxisomeproliferator-activated receptor-a)/RXR pathway [135]. Previously it has been found out that the effect of LPS on macrophages leads to a rapid dose-dependent increase in the expression of ABCA1 mRNA [180]. It has also been shown that infection Chlamydia pneumoniae infection reduces ABCA1 expression in A549 lung epithelial carcinoma cells [66].…”
Section: Other Mechanisms Of Abca1 Participation In Inflammationmentioning
confidence: 99%